Strategi Pengembangan Klaster Pengolahan Ikan Asin Pulau Pasaran Bandar Lampung - Zaini, Muhammad; Irfan Affandi, Muhammad; Haryono, Dwi (Politeknik Negeri Lampung, 2023)
Cluster approach is defined as one of the strategies to develop a competitive and sustainable of marine product prosessing industry. This study aims to develop a strategy for developing a salted fish processing cluster on Pulau Pasaran, Bandar Lampung, using a value chain approach. The research was conducted on Pulau Pasaran, Bandar Lampung in 2022 and is a survey research. The method for answering the research objectives is the SWOT analysis. The results showed that in order far the Pulau Pasaran fish processing cluster to increase its competitiveness and sustainability, it is necessary to improve quality and standardization, ease of technology for access to raw materials and markets. The development of processed salted anchovy clusters is designated as a regional superior commodity through unique packaging, so that the product is better known nationally and can meet the demand for salted anchovies in large quantities in international trade. In the long term, it is necesssary to establish a value chain network from line of supply, produsction, logistics, and distribution, to marketing with the involvement of supporting institutions from the capital sector and technology development support form related agencies.